Dissociation of ground and nσ* states of CF3Cl using multireference configuration interaction with singles and doubles and with multireference average quadratic coupled cluster extensivity corrections - Lucena Jr, Juracy R. (2007)
Extended complete active space self-consistent field (CASSCF), multireference configuration interaction with singles and doubles (MR-CISD), and multireference average quadratic coupled cluster (MR-AQCC) calculations have been performed on the ground (S0) and first excited (nσ*,S1) states of the CF3Cl molecule. Full geometry optimizations have been carried out for S0 as well as “relaxed” potential energy calculations for both states, along the C–Cl bond distance. Vertical excitation energies (ΔEvertical), dissociation energies (ΔEdiss), dissociation enthalpies (ΔHdiss), and the oscillator strength (f) have also been computed. Basis set effects, basis set superposition error (BSSE), and spin-orbit and size-extensivity corrections have also been considered. The general agreement between theoretical and available experimental results is very good. The best results for the equilibrium geometrical parameters of S0 (at MR-AQCC/aug-cc-pVTZ+d level) are 1.762 and 1.323 Å, for the C–Cl and C–F bond distances, respectively, while the corresponding experimental values are 1.751 and 1.328 Å. The ∠ClCF and ∠FCF bond angles are in excellent agreement with the corresponding experimental values (110.3° and 108.6°). The best calculated values for ΔEvertical, ΔHdiss, and f are 7.63 eV [at the MR-AQCC/aug-cc-pV(T+d)Z level], 3.59 eV[MR-AQCC/aug-cc-pV(T+d)Z level+spin-orbit and BSSE corrections], and 2.74×10−3 (MR-CISD/cc-pVTZ), in comparison with the corresponding experimental values of 7.7±0.1 eV, 3.68 eV, and 3.12×10−3±2.50×10−4. The results concerning the potential energy curves for S0 and S1 show a tendency toward the nonoccurrence of crossing between these two states (in the intermediate region along the C–Cl coordinate), as the basis set size increases. Such tendency is accompanied by a decreasing well depth for the S1 state. Dynamic electronic correlation (especially at the MR-AQCC level) is also an important factor toward an absence of crossing along the C–Cl coordinate. Further investigations of a possible crossing using gradient driven techniques (at CASSCF and MR-CISD levels) seem to confirm its absence.